Media studies: Evolution and perspectives - Kafle, Hem Raj (Bodhi: An Interdisciplinary Journal, 2010)
An interdisciplinary field of studies involves at least three concerns. The first is the question of its evolution from more than one origin. The second is its eclecticism - its reaches and scopes - the types of subjects, teachers, and students. And, the third is the general skepticism about its usefulness - the question of professionalism and employability. This essay is an attempt to address these fundamental concerns underlying the discourse on media studies as an interdisciplinary field. I first outline the academic and theoretical roots of this field. Then I discuss its major disciplinary dimensions and critical issues. DOI: 10.3126/bodhi.v3i1.2808 Bodhi Vol.3(1) 2009 p.10-20